Vegetable growing is one of the priority directions of agricultural production - V. F. Pivovarov; A. V. Soldatenko; O. N. Pyshnaya; S. M. Nadezhkin; L. K. Gurkina (Овощи России, 2020)
In recent years, in the agricultural sector there is a tendency to increase the production of crop products. However, its quality is still not high enough. To improve the situation in the vegetable growing industry, an important place is given to improving breeding and seed production, since the variety and high-quality seeds are the main elements of modern crop cultivation zonal technologies. At the Federal State Budgetary Scientific Institution “Federal Scientific Vegetable Center” (FSBSI FSVC), vegetable crop breeding has been put on the innovative path of development, where modern methods are used along with classical ones: molecular markers on the main of economical important plant determinants, accelerated creation of homogeneous lines using the methods of doubled haploids and biotechnology of functional products for healthy nutrition. As a result of purposeful selection work, domestic varieties and hybrids of vegetable crops with fundamentally new qualities were created. The geographical location of the branches of the Center allows you to create breeding achievements for all potential regions of vegetable growing. In 2019, 36 varieties and hybrids of vegetables and melon crops were created, including cabbage, carrot, tomato, onion, onion Shallot, perennial onion, garlic, peas, bean, cowpea, pumpkin, cucumber, sugar corn, green vegetables culture, spicy-flavouring plant and floral crops. In order to provide the industry with pure-grade quality seed material and increase the productivity of crops due to the full use of the potential of the variety in the FSBSI FSVC, constant work is carried out in primary seed production. Zonal cultivation technologies have been developed that will allow growing domestic products in different soil and climatic conditions of the country. Wide introduction of achievements of the Russian vegetable growing science in agricultural production is capable to provide the population of the Russian Federation with high-quality, domestic production.